Improving Insurance Operations in Nigeria Through the Digital Technologies - Adejumo, Wahab Adewuyi; Tijani, Adetunji Raimi (Archives of Business Research, 2022)
This paper aims to evaluate the impact of digitalization technologies on the insurance industry in Nigeria. Data were obtained from primary sources only. The primary data were collected through the mailed questionnaires that were administered to selected Chartered Insurers in Nigeria. The questionnaires were designed to reveal issues on digital transformation in Insurance industry in Nigeria. Seventy (70) questionnaires were sent to the respondents across the country in the six Geo-Political zones in Nigeria. It is noteworthy that 45% of the respondents were the Chief Executive Officers of different insurance companies, 30% of them were at Senior Manager Level of the Life Assurance Companies while the remaining 25% were the General Managers of Underwriting, Claims, Marketing and Human Resources Departments. It was found out that Nigerian Insurance companies as well as the NAICOM had transformed more than 40% of their services into digital technology. Besides, the research further revealed that almost every insurance company in Nigeria has a digital platform. The research recommends that the Federal Government should create sufficient budgetary allocation to invest in InsurTech and improve the training of the staff of the Government owned insurance companies such as NICON, Nigeria Reinsurance Corporation, LASACO, on the acquisition of digital skills. This will quickly encourage and mandate the private owned insurance companies to equally invest in InsurTech and arrange digital training for their staff so as to acquire digital skills necessary for the full digital transformation. The National Assembly should also amend the existing Constitutions on big data and recommend strict penalties for cybersecurity breaches. All these will disrupt the insurance services in Nigeria.